Determining the Attitudinal Disposition of Prospective Tertiary Admission seekers towards Open Distance Learning in Nigeria: Delta North in Perspective - Lucky, Amede (West African Journal of Open and Flexible Learning, 2016)
Open Distance Learning (ODL) has gained prominence and recognition in Nigeria because of its accessibility, flexibility and adaptability. It is an academic window that allows prospective tertiary admission seekers to actualize their educational interests and aspirations. The study attempted a determination of the attitudinal disposition of prospective tertiary admission seekers towards open distance learning in Nigeria: a case study of Delta North Senatorial District of Delta State. One research question and two hypotheses guided the study. The descriptive design was adopted for the study. The population of the study comprised all potential tertiary admission seekers in Delta North Senatorial District of Delta State and the sample of the study comprised 672 respondents (378 males and 294 females). The researcher employed a multi-stage sampling procedure. The instrument used for the study was a questionnaire titled: Attitudinal Disposition Inventory Questionnaire (ADIQ). The data collected were collated, coded and analysed using descriptive statistics and the independent sample t-test.  The outcome of the study revealed that the attitudinal disposition of potential admission seekers in delta North Senatorial District of Delta State towards ODL was indeed low. The two hypotheses were rejected and there was a disparity in the attitudinal disposition of potential admission seekers in Delta north Senatorial District of delta state towards ODL on the basic of locations ( Urban or rural) and gender (male and female).  A conclusion was drawn based on the discussions and useful recommendations were made, which include among others, that enough public enlightenment campaigns should be made by the government and ODL institutions to sensitize prospective tertiary admission seekers towards open distance learning.
Keywords: Attitudinal disposition; ODL; prospective tertiary admission seekers; synchronous learning; asynchronous learning